-6(-8x+4)=

Simple and best practice solution for -6(-8x+4)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(-8x+4)= equation:


Simplifying
-6(-8x + 4) = 0

Reorder the terms:
-6(4 + -8x) = 0
(4 * -6 + -8x * -6) = 0
(-24 + 48x) = 0

Solving
-24 + 48x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '24' to each side of the equation.
-24 + 24 + 48x = 0 + 24

Combine like terms: -24 + 24 = 0
0 + 48x = 0 + 24
48x = 0 + 24

Combine like terms: 0 + 24 = 24
48x = 24

Divide each side by '48'.
x = 0.5

Simplifying
x = 0.5

See similar equations:

| -15y+5x=30 | | 16.37+(-29.786)=y | | 3x=.5x+11 | | 5+32t-16t^2= | | -5.642-2.57=m | | -3+5+x=15 | | 15y+5x=30 | | 1x(4-3)=14 | | 3.9-36.24=z | | .40x=.5x-12 | | 25.9+(-4.3)=z | | -6(-3x+3)= | | 2x-4(x-4)=-2+5x-24 | | 56-(3c+4)=(c+5)+c | | 7b-8b= | | 7+4u+7=8u+6 | | 92c+5+3c=-75 | | 8+(1+x)= | | 125m-100m+35700=33425-150m | | 91x^2+x-2=0 | | 4x+56=449 | | 9t-1=17 | | 16=2x-1-x | | 4(g+5)=5(g-5) | | 3(2x-9)-3=3(x-4)+9 | | (2i+2)(4i-5)=0 | | 0.3+0.5x=2.3+x | | 144=3x+47+7x-13 | | 10=6+lnx | | -3(2x)= | | -560+(-40)=-600 | | -5n-4=-94 |

Equations solver categories